Synthesis And Characterization Of Complexes Of Transition Metals Mn(Ii), Co(Ii), Ni(Ii), Cu(Ii) And Zn(Ii) On Base Of 5-(3-Hydroxyphenyl)-1,3,4-Oxadiazoline-2-Thione - Razzokova, S.R., Kadirova, Sh.A., Muxidova, Z.Sh., Sadullayeva, G.B., Todjiev, J.N. (International Journal of Advanced Science and Technology, 2020)
The complex compounds Mn(II), Co(II), Ni(II), Cu(II) and Zn with 5- (3-hydroxyphenyl) -1,3,4-oxadiazolin-2-thione were synthesized and studied. By the methods of elemental analysis, scanning electron microscopy with energy-dispersive analysis, IR spectroscopy, differential thermal and X-ray analysis the composition and structure of the obtained complex compounds were established. Results of X-ray analysis of 5-(3-hydroxyphenyl)-1,3,4-oxadiazoline-2-thione monohydrate is included in the Cambridge Crystallographic Database (Cambridge Structural Database, https://doi.org/10.1107/S2414314619015323, deposit number CCDC 1965447)